United States reconstruction across the Americas - Link, William A. (Frontiers of the American South., 2019)
The book explores how emancipation, nationhood and nationalism, and the spread of market capitalism--all central to U.S. Reconstruction--were interwoven with patterns of post-Civil War global political, social, and economic developments.